Global existence and growth of solutions to coupled degeneratly damped Klein-Gordon equations - Fatma Ekinci; Erhan Pişkin (Al-Qadisiyah Journal of Pure Science, 2022)
We study a system of nonlinear Klein-Gordon equations with viscoelastic and degenerate damping in a bounded domain. We prove the global existence and exponential growth of solutions with negative initial energy.